In teaching the subject of complex numbers and operations on them use of historical data - Ummatova Makhbubakhan Akhmedovna; Tokhtabayeva Manzurakhan Mukhtarjonovna (Researchparks Publishing, 2023)
This article analyzes the knowledge, rule, evidence, law, theorem, definition, hypothesis necessary for the use of historical data in teaching the topic of complex numbers and operations on them. Examples of turns in the stages of development of mathematics are given. In the process of teaching, regular teaching of historical knowledge to students enables them to think independently, freely, to research, to approach each issue creatively, to feel responsibility, to carry out scientific research, to analyze, to make effective use of scientific literature. based on increasing their interests .